Gas-phase chemistry of technetium carbonyl complexes. Issue 20 (28th May 2015) - Wang, Yang; Qin, Zhi; Fan, Fang-Li; Haba, Hiromitsu; Komori, Yukiko; Cao, Shi-Wei; Wu, Xiao-Lei; Tan, Cun-Min
<x xml:space="preserve">Abstract</x> Relative chemical yields and adsorption enthalpies on quartz and Teflon surfaces for short-lived Tc carbonyl complexes were obtained.